In Vitro Antioxidant and Anti-Diabetic Potential of Gymnema Sylvestre Methanol Leaf Extract - A., Ibrahim; A., Babandi; A.A., Tijjani; Y., Murtala; H.M., Yakasai; D., Shehu; K., Babagana; I. A., Umar (European Scientific Journal, ESJ, 2017)
Some medicinal plants and their purified derivatives have demonstrated beneficial therapeutic potentials for many centuries. They have been reported to exhibit antioxidant activity, reducing the oxidative stress in cells and are therefore useful in the treatment of many human diseases, including diabetes and other non-communicable diseases. This study evaluated antioxidative activity and enzymatic (alpha-amylase and alphaglucosidase) inhibitory potentials of Gymnema sylvestre methanolic leaf extract (GSMLE) using standard methods. Phytochemical screening revealed the presence of alkaloids, tannins, saponins, steroids, terpenoids and flavonoids. The total phenolics and total flavonoids content in the extract were found to be 6.629±0.745 (µg/ml of catechol equivalent) and 0.004±0.0012 (µg/ml of quercetin equivalent) respectively. GSMLE was shown to have radical scavenging activity against DPPH (290.54 ± 39.72 %), hydroxyl radical (86.507 ± 23.55 %) and hydrogen peroxide (45.25 ± 25.23 %). The level of SOD was significantly decreased in H2O2 induced and H2O2+extract induced when compared with normal control (p<0.05); the level of GSH was significantly increased in H2O2 induced control and significantly decreased in H2O2+extract induced test when compared to normal control. GSH was also decreased significantly in H2O2+extract induced when compared to H2O2 induced control (p<0.05). The extract also demonstrated significant inhibition of alpha-glucosidase (IC50 182.26 ±1.05μg/ml) when compared with standard acarbose (IC50 189.52±0.46) and was more potent than the arcarbose on alpha-amylase inhibition with IC50 of 195.3±4.40 and 200.05±7.16 respectively. These findings may therefore, stress the potentiality of using Gymnema sylvestre as a natural remedy for the management of type 2 diabetes.